Interprofessional Care of Emergency Department Doctors and Pharmacists: Crossing a Collaboration Chasm - Jumana Al-Salloum; Dixon Thomas; Ghada AlAni; Baljinder Singh (University of Minnesota Libraries Publishing, 2020)
Role clarity of emergency department doctors and pharmacists is essential to provide collaborative care. Evidence is available that interprofessional care of doctor-pharmacist collaboration improves patient care in emergency settings. Pharmacists need to improve their knowledge and skill in emergency practice to be more productive and sought after. Team dynamics, training, and administrative support are critical. Interprofessional collaboration should not be programmed to fail for the short-term convenience of any profession. With more considerable effort from different stakeholders, once a collaborative system is established that will sustain improved patient care and the public trust of healthcare. Crossing a collaboration chasm takes time and effort. Interprofessional education should be built-in essential competencies to be collaborative with role clarity, teamwork, better communication, and ultimately patient-centeredness.   Article Type: Commentary